2015
DOI: 10.1136/medethics-2014-102619
|View full text |Cite
|
Sign up to set email alerts
|

The ethics of biosafety considerations in gain-of-function research resulting in the creation of potential pandemic pathogens: Table 1

Abstract: This paper proposes an ethical framework for evaluating biosafety risks of gain-of-function (GOF) experiments that create novel strains of influenza expected to be virulent and transmissible in humans, so-called potential pandemic pathogens (PPP). Such research raises ethical concerns because of the risk that accidental release from a laboratory could lead to extensive or even global spread of a virulent pathogen. Biomedical research ethics has focused largely on human subjects research, while biosafety concer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
35
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 35 publications
0
35
0
Order By: Relevance
“…A number of critics have argued that the risk of inadvertently creating a global pandemic through accidental release of an engineered, human-transmissible pathogen with high virulence and case fatality rate vastly outweighs any benefits that might be obtained from such research [e.g., 34]. Thus, one source claims a 0.01% to 0.1% probability per year of research in a BSL-3 lab of an accidental release of highly transmissible influenza virus that would kill between 200,000 and 16 million people [35,36].…”
Section: Accidental Release Of Highly Virulent Pathogensmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of critics have argued that the risk of inadvertently creating a global pandemic through accidental release of an engineered, human-transmissible pathogen with high virulence and case fatality rate vastly outweighs any benefits that might be obtained from such research [e.g., 34]. Thus, one source claims a 0.01% to 0.1% probability per year of research in a BSL-3 lab of an accidental release of highly transmissible influenza virus that would kill between 200,000 and 16 million people [35,36].…”
Section: Accidental Release Of Highly Virulent Pathogensmentioning
confidence: 99%
“…Similarly, comparisons of the risks of GOF research to the events leading to the development of the Nuremberg Code do not serve a useful purpose in the discussion [34]. The use of the word "Nuremberg" connotes an association with war crimes that is simply inappropriate for use in a rational discussion about experiments that are ostensibly being done by well-meaning scientists trying to prepare humanity for confronting a potential pandemic.…”
Section: Accidental Release Of Highly Virulent Pathogensmentioning
confidence: 99%
“…Despite this debate regarding the magnitude of biosafety risks posed by GOFR, there appears to be fairly widespread agreement that, other things being equal, research risks should be minimized (Casadevall et al 2014a, b; Casadevall and Imperiale 2014; DHHS 2013; Duprex et al 2015; Evans et al 2015; Imperiale and Casadevall 2015; Lipsitch and Galvani 2014; Lipsitch and Inglesby 2014). It has been suggested that GOFR risks might be reduced via:

Employment of safer pathogen strains

of low virulence,

for which there is immunity,

for which there are existing vaccines, and/or

which have been modified to inhibit replication outside of laboratories;

Development/use of vaccines against experimental pathogen strains;

Development/use of broad spectrum vaccines (e.g., pan- or universal influenza vaccine);

Vaccination of laboratory workers to create a ring of immunity; and/or

Ongoing improvement of biosafety practice and infrastructure.

…”
Section: Gain-of-function Research Ethics: State Of Debatementioning
confidence: 99%
“…In reaching this conclusion, they appeal to Nuremburg Code and Belmont Report requirements that research should “be done only if it benefits society, if the same benefits could not be procured through less risky means, and if the anticipated benefits exceed the anticipated risk” (Evans et al 2015). Though they acknowledge that the Nuremburg Code and Belmont Report were explicitly designed to govern research involving human subjects, they argue that (in light of the general ethical considerations upon which such guidelines are based) these requirements have broader applicability to risky research more generally.…”
Section: Gain-of-function Research Ethics: State Of Debatementioning
confidence: 99%
See 1 more Smart Citation